Analisis Komunikasi Strategis PT Pertamina Patra Niaga RJBT dalam Mengelola Brand Image pada Instagram - Savitry Ika Prasetyaningrum; Mardiana, Lisa (P3M Politeknik Negeri Media Kreatif, 2025)
This study analyzes the implementation of strategic communication by PT Pertamina Patra Niaga RJBT in managing brand image through Instagram. Using the Goals, Plans, and Actions (GPA) model, this research aims to explore communication objectives, strategic planning, and actions to enhance brand image. Data were collected through interviews with the company's social media team and literature review. The results show that PT Pertamina Patra Niaga RJBT successfully set clear goals, designed innovative content strategies, and selected appropriate media to reach the audience. Consistent actions and responsiveness to audience feedback played a key role in strengthening the brand image on Instagram. This study provides insights for companies on how to utilize social media as a strategic communication tool to build relationships with the audience and enhance brand image.